Hermeneutics of creeds and confessions: The question of continuity and change - Echeverria, Eduardo J. (Stellenbosch theological journal, 2015)
Modern culture has not really rendered creeds and confessions untrue; far less has it rendered them unbiblical. But it has rendered them implausible and distasteful. They are implausible because they are built on old-fashioned notions of truth and language. They make the claim that a linguistic formulation of a state of affairs can have a binding authority beyond the mere text on the page that creeds actually refer to something and that that something has significance for all of humanity.